Effect of bajijiasu isolated from Morinda officinalis F. C. how on sexual function in male mice and its antioxidant protection of human sperm. (22nd April 2015) - Wu, Ze-Qing; Chen, Di-Ling; Lin, Fang-Hua; Lin, Li; Shuai, Ou; Wang, Jin-Yu; Qi, Long-Kai; Zhang, Peng
Abstract: Ethnopharmacological relevance: In recent years, the physiological aspects of human fertility have been seriously influenced by the interactions of genetic and environmental factors. Almost one in 20 males has been affected by male infertility, providing a great challenge and an opportunity to use natural compounds as alternatives to chemical drugs with comprehensive adverse effects. However, ample evidences are scanty to support the physiological mechanisms of natural compounds used to treat male infertility. In traditional Chinese medicine, Morinda officinalis F. C. How is widely used as a herb that invigorates the kidneys and supports yang, the original energy in the human body, to resist diseases and in treating male infertility. In this study, we evaluated whether bajijiasu isolated from the roots of M. officinalis F.C. How is a potential agent for the treatment of male infertility. Materials and method: In this study, both normal and kidney-yang-deficient mice were administered bajijiasu orally at different concentrations. To determine the pharmacological mechanism of bajijiasu, we observed the sexual behavior and genital organ coefficients, determined their serum hormone levels, analyzed their sperm quality parameters, and examined histopathological sections from them. We also used enzymatic assays to determine the effects of bajijiasu on superoxide dismutase, glutathione peroxidase, and malondialdehyde. Confocal micro-Raman spectroscopy was used to investigate the changes in the DNA of H2 O2 -damaged human sperm after treatment with bajijiasu in vitro . Results: Our results showed that bajijiasu enhanced the sexual behavior of both normal and kidney-yang-deficient mice. It also markedly increased the testosterone concentrations, reduced the levels of cortisol, improved the quality of the sperm, and counteracted the histopathological impairment induced by hydroxyurea in the kidney-yang-deficient mice. The enzymatic assay and Raman spectra showed that bajijiasu protects the DNA of sperm from damage by H2 O2 . Conclusion: Bajijiasu is a potential androgen-like drug that modulates hormone levels to some extent without producing reproductive-organ lesions, enhances the sexual function of male mice, and protects the DNA of human sperm from H2 O2 damage. Thus, bajijiasu is an active ingredient of M. officinalis F.C. How that improves the human reproductive capacity. Graphical abstract: